Relações entre acuidade proprioceptiva, rigidez articular passiva e estabilidade funcional do tornozelo - Hellen Veloso Rocha Marinho (2014)
Ankle sprain is a common injury that affects this joints stability. Deficits in ankle proprioceptive acuity have been considered determinants for ankle functional instability. However, inconsistences found between these relationships question the contributions of proprioception to ankle stability. Recently, passive stiffness has been proposed as an important mechanism for forces propagations through the musculoskeletal system. This mechanism may also contribute to the perception of postures and movements. The aim of the present study was to assess how ankle ligament injury influences the proprioceptive acuity and the functional stability, and to assess the relationships among proprioceptive acuity, passive joint stiffness and functional stability in the presence of ankle ligament injury. Twenty-eight participants (male and female) age 23,75 ± 3,51 with and without lateral ankle sprain history were included in the study. The assessments included the threshold for movement perception (TMP), the passive-passive positional sense (PPPS), the ankles passive joint stiffness (APJS) and the star excursion balance test (SEBT). The participants with history of ankle ligament injury also answered the Cumberland Ankle Instability Tool (CAIT). Mixed ANOVAS were used to compare TMP, PPPS, APJS and SEBT measures between groups and limbs. Pre-planned contrasts were used to locate differences revealed by the ANOVA. Paired students t-test was used to verify functional stability (CAIT) differences between limbs for the participants with ankle ligament injury. Pearsons product-moment correlations were used to verify associations between the variables (TMP, PPPS, APJS, SEBT and CAIT) for the involved limb of the participants with ankle ligament injury. Differences between groups were found for the TMP, with the ankle sprain group demonstrating the worst performance. Interaction effect was also significant for this variable, with the injured limb having worse performance than the correspondent limb of the control group, however, no difference was found between limbs for the ankle sprain group. Differences were not found between limbs, groups or interaction for the variables PPPS and APJS. The results showed significant interaction effect for SEBT, with the injured limb presenting worse performance when compared to the non-injured limb. Associations between variables were not found. Based on the possible non-linear association between the variables, it was proposed a complementary analysis to reveal the possible influence of stiffness on proprioceptive acuity and the contribution of functional stability to proprioceptive acuity in the participants with ankle ligament injury. These participants were distributed into two groups: best proprioceptive acuity and worst proprioceptive acuity, the participants were diveded, based on the TMPs absolute errors, into percentiles 33,33% and 66,66%. Independent Students T-test didnt show any difference between theses groups for CAIT and SEBT variables. However, differences were revealed for the APJS. The best proprioceptive acuity group had higher APJS values than the worst proprioceptive acuity group. The results indicated that the ankle ligament injury influenced the subjects functional stability, which was not associated to proprioceptive acuity. The proprioceptive deficits found in the participants with ligament injury do not play any role in ankle joint stability and are, possibly, dependent on joint tissue stiffness.